Sources of Type I Interferons in Infectious Immunity: Plasmacytoid Dendritic Cells Not Always in the Driver's Seat - Ali, Shafaqat; Mann-Nüttel, Ritu; Schulze, Anja; Richter, Lisa; Alferink, Judith; Scheu, Stefanie (Frontiers in Immunology, 2019)
Type I Interferons (IFNs) are hallmark cytokines produced in immune responses to all classes of pathogens. Type I IFNs can influence dendritic cell (DC) activation, maturation, migration, and survival, but also directly enhance NK and T/B cell activity, thus orchestrating various innate and adaptive immune effector functions. Therefore, type I IFNs have long been considered essential in the host defense against virus infections. More recently, it has become clear that depending on the type of virus and the course of infection, production of type I IFNs can also lead to immunopathology or immunosuppression. Similarly, in bacterial infections type I IFN production is often associated with detrimental effects for the host. Although most cells in the body are thought to be able to produce type I IFNs, plasmacytoid DCs (pDCs) have been termed the natural “interferon producing cells” due to their unique molecular adaptations to nucleic acid sensing and ability to produce high amounts of type I IFN. Findings from mouse reporter strains and depletion experiments in in vivo infection models have brought new insights and established that the role of pDCs in type I IFN production in vivo is less important than assumed. Production of type I IFNs, especially the early synthesized IFNβ, is rather realized by a variety of cell types and cannot be mainly attributed to pDCs. Indeed, the cell populations responsible for type I IFN production vary with the type of pathogen, its tissue tropism, and the route of infection. In this review, we summarize recent findings on the cellular source of type I IFNs in different infectious settings, ranging from virus, bacteria, and fungi to eukaryotic parasites. The implications from these findings for the development of new vaccination and therapeutic designs targeting the respectively defined cell types are discussed.